PENERAPAN ACTIVITY BASED COSTING SYSTEM SEBAGAI DASAR PENETAPAN TARIF JASA RAWAT INAP PADA RUMAH SAKIT ROEMANI MUHAMMADIYAH SEMARANG - Mohammad Afifudin; R. Ery Wibowo Agung S (Universitas Muhammadiyah Semarang, 2013)
The purpose of this study was to gain knowledge about the determination of rates of hospitalization services using activity based costing, can be used as reference in setting tariffs inpatient services at Rumah Sakit Roemani Muhammadiyah Semarang and as means comparison with the rates of hospitalization for this set, as well as being one of that input provide information about activity based costing, especially in its application to a hospital that is the main orientation of community service. The method of analysis used descriptive method is to use the comparative analysis of the current hospital rates, set the cost method is based on activity based costing, and then compare the hospitalization rates based on activity based costing with its realization. The results showed that the calculation of hospitalization rates by using activity based costing, when compared with the rates used by the hospital activity based costing provides greater results for Class, IIB, PICU, dan BBRT and yields smallaer for class UTAMA, IA, IB,II, IIA, III dan R.BAYI. This is because the overhead loading on each product. On activity based costing, overhead costs for each product are charged to costs a lot of drivers. So that the activity based costing, has been able to allocate the cost of the activity room kesetiap appropriately based on the consumsion of aech activity.Keywords: activity based costing and cost driver.